Power system protection in smart grid environments - Bansal, Ramesh, author (Boca Raton : Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa, plc, 2019)
Includes bibliographical references and index